THE INFLUENCE OF ORGANIZATIONAL CULTURE AND TEAMWORK ON EMPLOYEE PERFORMANCE AT PT. BANK SULUT, TBK. - Robot, Chrestian (FEB Universitas Sam Ratulangi Manado, 2013)
Human resource is one of resources that determine the organization success. Because of that, organizations are demanded to manage the human resources well for the organization survival. With a support from upper level management, an employee works confidently in team and increases productivity of the organization. Basically, Bank Sulut is a government regional bank that has a wide network spread across several regions in Indonesia. To serve customers well Bank Sulut has a foundation of organizational culture that existing until today, which includes: fast serving of customers in more gentle way, treat customers as partners by developing better services, and consider about customers way of thinking in developing the services better. The research objectives is to analyze the influence of organizational culture and teamwork on employee performance. Organizational culture is shown by the values, traditions, and behaviors that employees share in their organizations. A team is an identifiable set of two or more individuals interacting within a larger organizational context to reach a common goal through specific interdependent roles and task boundaries. In this research is found that Employee maximum performance is needed in running a good organization, the more maximize employee performance the better the organization will be. Keywords: organizational culture, teamwork, employee performance.